First record of the leafhopper genus Subhimalus Ghauri, 1971 (Hemiptera: Cicadellidae: Deltocephalinae) from China, with description of a new species - Xing, Ji-Chun; Dai, Ren-Huai; Li, Zi-Zhong (Zootaxa, 2011)
The genus Subhimalus Ghauri, 1971 is reported for the first time and a new species Subhimalus attenuatus sp. nov. is described and illustrated from China. A key is given to distinguish all species of the genus. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).